Effect of Diversity in the Board of Directors and Top Management Team on Corporate Social Responsibility - Priscila Prudêncio; Hyane Forte; Vicente Crisóstomo; Alessandra Vasconcelos (BBR: Brazilian Business Review, 2021)
This study analyzes the effect of corporate governance, with an emphasis on gender and age diversity in the board and Top Management Team, on Corporate Social Responsibility in Brazil. The sample was composed of Brazilian firms with corporate governance published in the CVM reference form, financial information in the Economática® database, and CSR assessed by the CSRHub database, in the 2016-2017 biennium, with a total of 194 firm-year observations. Diversity is measured by the presence of women, age heterogeneity, and average age in the board of directors and top management team. The results indicate that gender diversity in the board of directors and the higher average age of the top management team have a favorable effect on the CSR practices of Brazilian firms. Additionally, it was observed that age heterogeneity among board members has a negative influence on CSR practices. The research contributes to a better understanding of the behavior of more diverse boards of directors and top management teams regarding CSR strategies.